Laporan Kasus Endoftalmitis et causa Ulkus Kornea Perforasi Okuli Sinistra - Rani Himayani; Ratu Faradhila Jonis (CV. Jasa Sukses Abadi, 2021)
Endophthalmitis is purulent inflammation of the entire intraocular tissue, accompanied by the formation of an abscess in the glass body. If there is further inflammation that affects the third wall of the eyeball, this condition is called panophthalmitis. Endophthalmitis is divided into endogenous endophthalmitis (spread of pathogens into the eye through systemic) and exogenous endophthalmitis (pathogens enter through mechanisms such as eye surgery, open trauma, and intravitreal injections). This case report describes endophthalmitis et causa. corneal ulcer perforation ocular sinistra in 41-year-old male due to eye trauma. Management in these patients is pharmacotherapy to reduce initial symptoms and operative measures in the form of eviseration.